Water and solutes in soil : hydraulic characterisation, sustainable production, and environmental protection : application for the degree of Doctor of Science from Massey University, Palmerston North, New Zealand - Clothier, Brent E (Massey University, 2002)
The soil of the rootzone, the fragile and fertile interface between the atmosphere and the subterranean realm, is characterised by massive transfers of water and solutes. Our understanding of the biophysical transport processes into, and through, soil has been enhanced by the research endeavours of the applicant, Brent Euan Clothier. Dr Clothier, a 1977 Ph.D. graduate of Massey University, has developed tools and techniques that increased the acuity of our vision of transport processes of water and solutes in soil, as well it has sharpened our ability to hydraulically characterise those mechanisms for the purpose of modelling and risk assessment. His research has also enhanced our understanding of how these biophysical processes affect sustainable agriculture, environmental protection, and the bioremediation of contamination. These endeavours are grouped, in this thesis, into four overlapping areas of research: • Processes and properties of water movement into and through soil • Processes and properties of solute movement through soil • Root uptake processes and sustainable irrigation • Plants, groundwater protection and bioremediation of contaminated soil. The key elements of these four themes, and their contribution to knowledge, form Chapters 2-5 of this thesis. Dr Clothier's awards, honours, and impact are discussed in Chapter 6.
This Doctor of Science comprises a number of published works listed in the Bibliography in the attached file. Due to copyright restriction, they are not included here but can be accessed individually from the publisher.
Keywords: Bioremediation; Groundwater; Plant-soil relationships; New Zealand; Soil moisture; Soil physics; Soils; Solute movement